Modelling of the effect of a thin stiffener on the boundary of a nonlinear thermoelastic plate - Rahmani, Leila (Mathematical Modelling and Analysis, 2009)
We consider a dynamic nonlinear model for a heterogeneous thermoelastic plate consisting of a thin highly rigid body of high thermal conductivity perfectly glued on a portion of the boundary of an elastic plate. This model, which describes the nonlinear oscillations of a plate subjected to thermal effects is referred to as the “full von Karman thermoelastic system”. Our aim is to model this junction and reproduce the effect of the thin body by means of approximate boundary conditions, obtained by an asymptotic analysis with respect to the thickness of this body. First published online: 14 Oct 2010